Developing a laboratory exercise using virtualization technology for a system administration course: case of Kolej Universiti Islam Antarabangsa Selangor (KUIS) / Khairil Ashraf Elias @ Mayah - Elias @ Mayah, Khairil Ashraf (2012)
System Administration is a field that demands understanding in computer and network system such as operating system, application, networking, hardware, security and troubleshooting technique. Real-time and hands-on practical exercise will give students the opportunity to apply and integrate system administration skills they have learned during lecture class. However it is impractical and expensive to setup a dedicated and conventional hardware based lab especially for institution with limited monetary budget. The alternative way of teaching Linux System Administration course is Virtual Based Lab where specific tools are used to represent real IT infrastructure. The Virtual Laboratory (VLAB) project was initiated at Kolej Universiti Islam Antarabangsa Selangor (KUIS). The main aim of this project is to develop a laboratory exercise using virtualization technology for System Administration Course which is currently taught at KUIS as a part of Diploma in Computer Science program. It will provide a safe platform for the student to learn basic system administration. The project objective is achieved by doing critical analysis on different types of virtualization technology before choosing one that best meets the requirements. User Centered Design Approach has been a guideline in project development methodology to ensure that every phase involved will primarily focus on user requirement. Apart from the development of VLAB web application, the project uses Proxmox VE; an open source virtualization solution as the virtualization core engine to provide virtual machine instances to the students. Students can now perform laboratory experiment on KUIS VLAB using web browser from any computer connected to the Internet. As a result the project has successfully encouraged students to explore Linux operating system and motivate them into using KUIS VLA Bas a training platform for their System Administration activities.